(untitled) (قضايا سياسية, 2023)
Despite having left the office in September 2020, Shinzo Abe's legacy will most likely continue to dictate Japan's foreign and security policy for years to come. Throughout his long tenure, Shinzo Abe progressively, by employing multifaceted approaches, succeeded in changing Japan's prolonged tradition of pursuing pacifist policies. Building on long-term trends of reforms, Shinzo Abe made those reforms an integral part of Japan's political agenda when he assumed power as prime minister in December 2012. The contemporary global and regional challenges that Japan has faced during the last few years prompted the Shinzo Abe administration to accelerate and expand the transformation of Japan’s prolonged tradition of following pacifistic approaches in the global arena as those traditions were restricting Japan from undertaking an active role internationally. Shinzo Abe sought to loosen the shackles that restricted his country's security policies and hindered its ability to assume a more active role in international politics since the end of the Second World War. Abe’s approach took the shape of institutional and legislation revisions, a reinterpretation of constitutional articles, deepening bilateral and multilateral relations and alliances, and increasing Japan’s military capabilities. Despite the fact that Shinzo Abe’s policies were of transformational nature, they can be positioned within a long string of incremental adjustments that shifted Japan's foreign and security policy from pacifism toward more 'assertive' and realistic trajectories.